O partido federalista na primeira república brasileira : imprensa e discursos parlamentares - Rouston Junior, Eduardo (2016)
This paper aims to examine, through the prism of the press and parliament, the political role of the Federalist Party in the context of the First Brazilian Republic. From this analysis two points jump in sight: first, to defend the strengthening of representative government, set within the framework of a parliamentary Republic and, secondly, the strengthening of the federal Union on the state units by delivering a political centralization regime for the Brazilian state. These two main aspects that stand in the federalist speech at the national level, were strongly influenced by a regional character problems, experienced by Rio Grande do Sul during the castilhista-borgista regime of authoritarian and conservative feature: with respect to the southern state, denial that the castilhista situationism was around the representative government and its replacement by a "dictatorship"; with regard to the Union, the desired subject of this authoritarian interests of Chief Rio Grande State. In this sense, we analyze, through political press and parliamentary speeches of federalist opposition, the relationship had major thematic policies raised by maragato party at the national level with the situation south of Rio Grande, occasioned by castilhista-borgista authoritarianism, which the Federalist Party, throughout its history, has always been energetic opponent.